Bottom‐Up Formation of Dodecane‐in‐Water Nanoemulsions from Hydrothermal Homogeneous Solutions1. Issue 25 (13th May 2013) - Deguchi, Shigeru; Ifuku, Nao
<x xml:space="preserve">Abstract</x> Only 10 seconds: Hydrocarbons and water do not mix under standard conditions, but they do mix freely at high temperature and high pressure near the gas/liquid critical point of water (Tc=374 °C, Pc=22.1 MPa). Quenching of homogeneous solutions of dodecane and water at such extreme conditions in the presence of a surfactant results in bottom‐up formation of nanosized oil droplets in water in only 10 seconds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>